Le retour du naturel : regards insulaires à partir de l’archipel des Galapagos et des petites îles de Méditerranée - Orianne Crouteix; Josselin Guyot-Téphany (Bulletin de l’Association de Géographes Français)
Geography has evolved through the proliferation of epistemological approaches, which led to a split between physical and natural geography in the mid-20th century. We retrace this history focusing on the way islands shaped the relationships between geography, natural sciences and conservation policies since they held a major place in building these knowledges and policies. We show the persistence of the naturalistic rhetoric in environmental policies despite the emergence of sustainable development’s typical movement toward integration. Then, through a comparative study of our respective field - the Galapagos archipelago and the small Mediterranean islands - we highlight the (re)mobilization of this rhetoric by scientific and political stakeholders. Our in-depth immersion in naturalistic structures and participation to operational projects, allows us to point out the limits of the geography’s integration as human sciences to overcome the conservationist model, while this scientific field appears as one of the most relevant to build an alternative way to naturalism.